ADAPTASI MASYARAKAT TERHADAP PERUBAHAN LINGKUNGAN (STUDI PADA MASYARAKAT YANG TINGGAL PADA KAWASAN PETERNAKAN AYAM PETELUR DI KANAGARIAN TIGO JANGKO KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR) - Aldi Syahputra; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The presenting of chicken egg layer industrial in society areahave many positives and negatives impact toward the society itself. So the society should be able to agree with them self toward the changing of environment. This research was conducted inTigo Jangko village, Lintau Buo sub district, Tanah Datar regency, Sumatera Barat. The aim of this research is to know the adaptation level of society toward the changing of environment and the pattern of social relationship between the owner of chicken egg layer with the society in Tigo Jangko village. This is descriptive qualitative method. Descriptive qualitative is the research which is aim to show the fact, situation and others phenomena. Thus the writer will apply the concept, collect the data and fact in research area. The techniques are interview and observation. While, the techniques analysis data are data collection, data reduction, showing the data, conclusion and suggestion. The result of the research is the adaptation level of society influenced by some criteria such as the distance of house from chicken egg husbandry, how long they live in, the smell of egg feces, the noise of the chicken, and the voice of rolling corn machine and contamination of environment. Thus from this phenomena it can be classified the adaptation level of society are high and medium. They are many adaptation strategies which are done by society to face the changing of environment. Egg layer husbandry in society environment Tigo Jangko village appears many balance relationship, for example giving education donation, food donation, sympathetic care of fatherless child, dhua’fa, social donation, job field, buying the egg with cheaper price and social interaction between husbandry owner with the society in various aspects.Keywords: The changing of environment, adaptation, and social changing